Multiple Ovulation and Embryo Transfer in Kenya: A Review of the Success Rates and Lessons Learnt - Kios, D. K.; Kitilit, J. K.; Oliech , G. O.; Ongubo , M. N.; Rachuonyo , H. A.; Ndiema, M. K. (African Journal of Education,Science and Technology (AJEST), 2013)
There is a high demand for high producing dairy cows in Kenya and in the East African region. Milk plays an important role in human nutrition especially provision of cheaper much needed proteins, minerals and other nutrients. It is also a source of income to many households and the people employed within the dairy farms. The livestock sector contributes 10-12% of the gross domestic product (GDP), which represents 47% of the Agricultural GDP, in Kenya. Dairy farming contributes over half of these through milk production and sale of breeding stock. Over 80% of all milk is produced by small scale farmers in rural areas who depend on large scale breeders to provide affordable replacement heifers. The use of assisted reproductive techniques including artificial insemination, sexed semen, multiple ovulation and embryo transfer and invitro embryo production has propelled many countries to achieve sustainable production of milk and replacement heifers. Commercial cattle embryo transfer in the world was established during the early 1970s. It is difficult to have adequate and high quality replacement heifers due to low reproductive capacity and inadequate number of high quality breeding stock in Kenya. Attempts to bridge this gap with newer biotechnologies including multiple ovulation and embryo transfer (MOET) have had variable success rates. This has led to higher cost of production thus discouraging the adoption of such high value technologies. The aim of the review was to evaluate the MOET technology since its introduction to Kenya in the 80s. The super ovulations resulted in variable embryo production with a range of 0 to 13 transferable embryos and successful transfer rates between 0 to 67%. Lack of an appropriate MOET protocol, poor choice of donors and recipients, poor technique and lack of finance were among the factors that have contributed to the observed variations. Reproductive efficiency of the top producing cows through MOET may provide a solution to the high demand which has driven the prices of breeding cattle way above the ordinary milk producer.